MORTALITY PATTERN IN BUFFALO CALVES IN ORGANIZED FARMS OF TAMIL NADU - Kumar, Vasantha; Sivakumar, T; Ramesh, V; Edwin, SC (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The mortality pattern in Murrah and Surti buffalo calves was studied for a period of 11 years (1991- 2001) from the available records in certain organized farms of Tamil Nadu for four seasons viz. hot, south west monsoon, northeast monsoon and cold seasons. Data pertaining to 471 death records of buffalo calves were collected and analyzed. High (P<0.05) percentage of mortality occurred in male (18.58 ± 0.82, 20.20 ± 0.58) than the female (14.31 ± 0.53, 19.65 ± 0.59) calves in both Murrah and Surti graded respectively. The Surti graded showed heavier (P<0.01) losses than the Murrah calves. High (P<0.01) calf losses during cold season (11.37 ± 2.01), followed by northeast monsoon (9.50 ± 1.11) for Murrah and cold (14.27 ± 1.66) and northeast monsoon (9.80 ± 1.20) for Surti graded buffalo were noticed. The incidence of pneumonia and enteritis was 39.19 and 24.91 in cold season, 32.17 and 16.79 per cent in hot, 30.67 and 25.33 per cent in northeast monsoon, 27.17 and 21.00 per cent in southwest monsoon which caused maximum mortality in buffalo calves.